Copper - Kibuishi, Kazu (New York Graphix/Scholastic, 2010)
Copper is curious, and Fred is fearful. And together boy and dog are off on a series of adventures powered by Copper's limitless imagination. The two friends have a knack for getting into all sorts of odd situations, but Copper's good cheer always smoothes the way--and Fred can usually be won over if there's food involved
Hurg
5
Keywords: Boys -- Comic books; Dogs -- Comic books; Friendship -- Comic books